Management of malnutrition in older patients: current approaches, evidence and open questions - Volkert, Dorothee; Beck, Anne Marie; Cederholm, Tommy; Cereda, Emanuele; Cruz-Jentoft, Alfonso; Goisser, Sabine; de Groot, Lisette; Großhauser, Franz; Kiesswetter, Eva; Norman, Kristina; Pourhassan, Maryam; Reinders, Ilse; et al. (Journal of Clinical Medicine, 2019)
Malnutrition is widespread in older people and represents a major geriatric syndrome with multifactorial etiology and severe consequences for health outcomes and quality of life. The aim of the present paper is to describe current approaches and evidence regarding malnutrition treatment and to highlight relevant knowledge gaps that need to be addressed. Recently published guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN) provide a summary of the available evidence and highlight the wide range of different measures that can be taken—from the identification and elimination of potential causes to enteral and parenteral nutrition—depending on the patient’s abilities and needs. However, more than half of the recommendations therein are based on expert consensus because of a lack of evidence, and only three are concern patient-centred outcomes. Future research should further clarify the etiology of malnutrition and identify the most relevant causes in order to prevent malnutrition. Based on limited and partly conflicting evidence and the limitations of existing studies, it remains unclear which interventions are most effective in which patient groups, and if specific situations, diseases or etiologies of malnutrition require specific approaches. Patient-relevant outcomes such as functionality and quality of life need more attention, and research methodology should be harmonised to allow for the comparability of studies.
Gesehen am 23.07.2020